Honorific Words in Japanese and Balinese Languages: A Case Study of Social Interaction Dynamics - Ida Ayu, Putri Gita Ardiantari; Meidariani, Ni Wayan; Andriyani, Anak Agung Ayu Dian (Pusat Kajian Humaniora FBS Universitas Negeri Padang, 2025)
Honorifics are words that show respect and politeness. They are important in languages like Balinese and Japanese because they reflect the culture and social rules of the society This study aims to examine the use of honorifics in Balinese and Japanese languages, with a focus on their dynamic role in everyday communication. The research investigates how honorific expressions reflect cultural norms, social hierarchies, and interpersonal relationships in both linguistic contexts. A qualitative comparative method was employed, using data collected from native speakers through participant observation, and structured interviews. The primary sources of data include recorded conversations, cultural texts, and interviews with Balinese and Japanese speakers. Data collection techniques involved field study and discourse analysis, while the data were analyzed using sociolinguistic and pragmatic frameworks. The results showed that Balinese honorifics come from traditions like caste, age, and social status, while Japanese honorifics depend more on the situation and how people relate to each other, influenced by context and the nature of interpersonal relationships. These results highlight the role of honorifics in maintaining social harmony and expressing cultural values. The study contributes to a deeper understanding of politeness strategies across cultures and offers insights for cross-cultural communication and sociolinguistic research